Modulation of Lung Retinoid Metabolism and Signaling by Smoking in a Guinea Pig Model - Somdutta SinhaRoy; Michael Schäffer; Shyamali Mukherjee; Salil K Das (The FASEB Journal, 2006)
Vitamin A (retinol) and its active metabolites (retinoic acids) are important for growth and differentiation of various cell types. Retinoids are known for their role in prevention of carcinogenesis and have been shown to be effective inhibitors of chemical carcinogenesis in epithelial tumours such as those of the skin, lung, breast, prostrate, cervix, bladder and oesophagus. Our laboratory has previously reported that the guinea pigs which were forced to inhale cigarette smoke accumulated retinol (combined retinol and retinyl ester) in lung. In the present study, we have developed a sensitive HPLC method for analysis of all retinoids (both polar and non‐polar) in a single run. The guinea pigs were divided into three groups namely sham control (SH, without smoke), side stream (SS, side stream smoke) and mainstream (MS, main stream smoke). The results show that retinyl esters are accumulated in MS lung. Western blot analyses of the lung homogenate also showed that smoking modulated other enzymes and proteins involved in the retinoid signaling pathway like CYP 26 and RAR β. This study gives us an insight into putative candidates for therapeutic prevention of lung cancer due to smoking. (Supported by US Army Grant DAMD17‐03‐1‐0352 and DAMD17‐03‐2‐0054)